Effect of the alveolate parasite Perkinsus olseni infection on sexual maturation and spawning efficiency of the clam Ruditapes decussatus. Issue 4 (1st April 2023) - Fernández-Boo, Sergio; Duarte, Catarina; Guévélou, Eric; Sousa, Joana; Freitas, Rosa; Joaquim, Sandra; Costas, Benjamin; Magalhães, Luisa; Matias, Domitília; Cruz, Andreia
Abstract: Abstract: The effect of Perkinsus olseni infection on the reproduction ability of clams has been underestimated so far. Although some studies found evidence of reduction of egg production and delay in gonad maturation after infection, the total effect of the infection is still unclear. In this study, Ruditapes decussatus clams from a naïve population were injected with two different doses of P. olseni parasites, a low dose leading to a light infection and a high dose leading to a heavy infection. Clams were maintained during 2 months for maturation, and at the end of the experiment, the spawning was induced, the number of larvae release and mortality were evaluated. During the maturation period, infection level, gonadal stage, condition index, gross biochemical composition and oxidative status of progenitors were evaluated at days 0, 30 and 60 post-injection. The effects of P. olseni infection on clams showed alterations on biochemical parameters, namely lipid peroxidation, a significant mortality and a delayed gonad maturation, with a greater effect in the highly infected individuals. The reproductive capacity of the clams was impaired in both infected groups showing a lower production and a higher mortality rate of larvae. Finally, this study indicates that the production of natural beds with a high prevalence of P. olseni could be compromised by a deregulation of the natural reproduction cycle and a decrease in larvae production by infected animals, probably due to a combination of lower egg production and lower lipid reserves in larvae from infected clams.